Allelopathic Effect of Aqueous Extract of Parkia Biglobosa (L.) on Some Weeds in Gombe State, Nigeria - Jedidah Akawu Jacob; Bappah-yaya Usman; Cleophas Billah Ajiya (Turkish Journal of Agriculture: Food Science and Technology)
This study examined the allelopathic effect of different concentration of aqueous extracts of Parkia biglobosa stem bark on the germination and growth of weed seeds species. Seeds of Eragorastis tenella, Eragorastis atrovirens, Pannicum pedicellata, Pennisetum sub albidum, Hypharrhenia rufa and Brcichiaria brizantha were tested for plumule germination and radicle growth with three different concentrations of 1%, 5%, 10% plant extract while ordinary water was used as control. Growth parameters including germinated weeds population were measured; the highest germinated weeds population was at the control (8.06±3.97) and the least was obtained from the 10% concentration with the mean of (4.42±2.59). Weeds population decreased as the concentration increased. The highest mean of weeds height was recorded from 1% concentration (11.46±7.08) which is statistically significant while the least mean was recorded from 10% concentration (7.69±6.70) statistically not significant. The family emergence by concentration indicated that, the experiment under control had (4 families) for 1% (2 families), 5% (2 families) and 10% (4 families) emerged. The germination, radicle and plumule length were inhibited when compare with control and the inhibition was statistically not significant at.